Self-Assembling Networks. (22nd August 2017) - Barrett, Jeffrey A; Skyrms, Brian; Mohseni, Aydin
Abstract: We consider how an epistemic network might self-assemble from the ritualization of the individual decisions of simple heterogeneous agents. In such evolved social networks, inquirers may be significantly more successful than they could be investigating nature on their own. The evolved network may also dramatically lower the epistemic risk faced by even the most talented inquirers. We consider networks that self-assemble in the context of both perfect and imperfect communication and compare the behaviour of inquirers in each. This provides a step in bringing together two new and developing research programmes, the theory of self-assembling games and the theory of network epistemology. 1 Introduction 2 The Basic Model 3 Equilibrium Analysis 4 Perfect Communication 5 Imperfect Communication 6 Discussion 7 Conclusion